Analisis Strategi Pemberian Kredit Dalam Upaya Mencegah Kredit Bermasalah (Non Performing Loan) Pada PT Bank Rakyat Indonesia (Persero) Tbk - Sari, Nanda Widiya; Fitrianingsih, Fitrianingsih; Saragih, Wulandari; Siregar, Attila Rania Insiyah; Husna, Asmaul (Accounting Progress, 2025)
The research aims to analyze credit granting strategies to prevent Non-Performing Loans (NPL) at PT Bank Rakyat Indonesia (Persero) Tbk (BRI). The research focuses on reviewing strategies using the 6C approach (Character, Capacity, Capital, Collateral, Condition, and Constraints) in the credit granting process to minimize the risk of default. Additionally, a historical data analysis of the NPL ratio is conducted, comparing non-performing loans to the total credit granted. The findings indicate that consistently implementing the 6C approach significantly reduces the NPL level, particularly through strict evaluations of customer characteristics, financial capacity, and credit collateral. This study provides valuable insights into credit risk management and the formulation of more effective strategies to maintain BRI's financial stability amid dynamic economic challenges.